Effectiveness and drug adherence of biologic monotherapy in routine care of patients with rheumatoid arthritis: a cohort study of patients registered in the Danish biologics registry. (13th July 2015) - Jørgensen, Tanja Schjødt; Kristensen, Lars Erik; Christensen, Robin; Bliddal, Henning; Lorenzen, Tove; Hansen, Michael S.; Østergaard, Mikkel; Jensen, Jørgen; Zanjani, Lida; Laursen, Toke; Butt, Sheraz; Dam, Mette Y.; et al.
Abstract: Objectives. To estimate the prevalence of Danish RA patients currently on biologic monotherapy and compare the effectiveness and drug adherence of biologic therapies applied as monotherapy. Methods. All RA patients registered in the Danish biologics database (DANBIO) as receiving biologic DMARD (bDMARD) treatment as monotherapy without concomitant conventional synthetic DMARDs (csDMARDs) during the study period 1 May, 2011 through 30 April 2013 were eligible for inclusion. All patient files were checked to ensure that they were in accordance with the treatment registration in DANBIO. Descriptive statistics for prevalence, effectiveness and drug adherence of bDMARD monotherapy were calculated. Results. Of the 775 patients on bDMARD monotherapy, adalimumab (21.3%), etanercept (36.6%) and tocilizumab (15.3%) were the most prevalent biologic agents administered. At the 6-month follow-up, the overall crude clinical disease activity index remission rate in patients still on a biologic drug was 22%, the 28-joint DAS remission rate was 41% and the response rate of those with a 50% improvement in ACR criteria was 28%. At the 6-month follow-up, the drug adherence rates were similar for the different bDMARDs, with the exception of infliximab, which had significantly poorer drug adherence ( P < 0.001). The overall drug adherence (except for infliximab) was approximately 70% after 2 years. Conclusion. Nearly one in five (19%) biologic treatments for RA was prescribed in Denmark as monotherapy, of which 70% were on monotherapy from bio-initiation and 30% were on monotherapy after cessation of a concomitant csDMARD. Acceptable drug adherence and remission rates were achieved with bDMARDs. With the exception of infliximab, no statistically significant differences were observed between anti-TNFs and biologics with other modes of action.